Formulation of Health Boosting Foods by Exploring the Microbial Wealth Harbouring in Ethnic Food System of Indian Himalayas - Gautam, Neha; Sharma, Nivedita; Ahlawat, Yogesh K.; Sharma, Nisha (Flavour and fragrance journal, 2025)
Nowadays, traditional food/ethnic foods have vanished from the diet of majority of young people. There is a need to preserve endangered and rarely used fermented food items to maintain the good health of future generations. Therefore, there is a scope for food industry to make an effort to explore nutrient rich sources out of these rarely used foods. The blending of ethnic and traditional foods in a scientific way could trigger many cumulative foods adding fresh dimensions simultaneously preserving functional properties of these foods and providing health benefits. The Himalayan states harbours more thousands types of fermented foods/ethnic foods being consumed. The majority of food consumed by the population in remote areas of the country includes a variety of ethnic dishes from the Indian Himalayas, such as Sepu Bari, Seera, Salori, Bhaturu, Aenkali, Childa‐bhala, Gundruck, Dhulliachar, Jaanr, Angoori, Chuli, Auria, Jhol, Chhang and Churpi. These foods have seldom been explored for their potential to yield new and health‐promoting microorganisms. For the first time, the aforementioned items have been investigated for the isolation and identification of safe, food‐grade bacteria, paving the way for the development of innovative health foods with functional properties.